Consuming Latinidad? The Politics of Food, Consumption, and Troubling Latina Identity in Alisa Valdés-Rodríguez's The Dirty Girls Social Club. Issue 5 (20th October 2017) - Herrera, Cristina
ABSTRACT: Alisa Valdés-Rodríguez's best-selling 2003 novel, The Dirty Girls Social Club, marketed as "chica lit, " a Latina version of famous "chick lit, " such as Bridget Jones's Diary and Sex and the City, presents us with what is characterized as "troubling" Latina identity that only partially succeeds in transforming Latina stereotypes. While a number of literary scholars have examined Dirty Girls, none have fully considered Valdés's equally troubling portrayal of another form of consumption: dining. Food is consumed by the characters, or " sucias /dirty girls, " as they call themselves, in amounts ranging from excessive to minuscule; as I argue, their attitudes about food, eating, and certain dining establishments reflect their complex, troubling expressions of Latina identity. Through an analysis of the novel's treatment of food, dining, and consumption, I examine the characters' troubling Latina identity as they (at times) futilely reject stereotypes of Latina women.